Diplomatic training in the Republic of belarus: History, ‘Entry Points’ and Epistemic Community - E. V. Pilgun; O. N. Leshenyuk; A. S. Boyashov (Международная аналитика)
The article is devoted to the issues of training International Relations (IR) students in the Republic of Belarus. It analyzes the process of training future diplomats, reflects the features of language training, gives an insight into the history of training, and describes the main areas of cooperation between Belarusian universities and the Ministry of Foreign Affairs of the Republic of Belarus. The training of diplomats is characterized by interdisciplinarity, the use of advanced technologies, and a high degree of motivation for continuous learning. Modern programmes for training international relations specialists include not only traditional disciplines, but also practical skills and tools (including soft skills) that allow them to effectively cope with the variety of challenges facing the international community. In the context of globalization and digitalization, fundamental knowledge remains an important aspect of diplomatic training. Since the early 1990s, Belarus has been actively developing its own system of training diplomatic personnel, based on universities and the special role of a centralized system of selection and language retraining of future diplomats.